Evidence of weak conscious experiences in the exclusion task - Sandberg, Kristian; Del Pin, Simon H.; Bibby, Bo M.; Overgaard, Morten (Frontiers in Psychology, 2014)
Exclusion tasks have been proposed as objective measures of unconscious perception as they do not depend upon subjective ratings. In exclusion tasks, participants have to complete a task without using a previously presented prime. Use of the prime is taken as evidence for subliminal perception, yet it may also simply indicate that participants have weak experiences but fail to realize that these affect the response or fail to counter the effect on the response. Here, we tested this claim by allowing participants to rate their experience of a masked prime on the Perceptual Awareness Scale (PAS) after the exclusion task. Results showed that the prime was used almost as often when participants reported having seen a ‘weak glimpse’ of the prime as when they claimed to have ‘no experience’ of the prime, thus suggesting participants frequently have weak (possibly contentless) experiences of the stimulus when failing to exclude. This indicates that the criteria for report of awareness is lower (i.e. more liberal) than that for exclusion.